2009
DOI: 10.3358/shokueishi.50.47
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone Contamination and the Causative Fungi in Sorghum

Abstract: Natural contamination by zearalenone, a toxic metabolite of Fusarium fungi, was surveyed in 160 samples of sorghum imported from 2001 to 2006 into Japan for feed. Of these 160 samples, 84 (52.5῍) were contaminated with zearalenone, ranging in concentration from 60 to 7,260 mg/kg. In the contaminated sorghum samples, F. semitectum, F. verticillioides, F. oxysporum, and other Fusarium spp. were detected. The concentration of zearalenone was well correlated with the development of colonies of F. semitectum and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The standards of ZEN and the 5 ZRCs were purchased Fungal strain studied F. semitectum was isolated from sorghum as previously described 20) . Briefly, ground sorghum was homogenized in 0.1 peptone-water.…”
Section: Standards and Reagentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The standards of ZEN and the 5 ZRCs were purchased Fungal strain studied F. semitectum was isolated from sorghum as previously described 20) . Briefly, ground sorghum was homogenized in 0.1 peptone-water.…”
Section: Standards and Reagentsmentioning
confidence: 99%
“…ZEN and the 5 ZRCs were extracted and purified according to the ZEN production assay for Fusarium species as previously described 20) . In summary, ZEN and the ZRCs in the purified solution were determined by LC-MS with an atmospheric pressure chemical ionization (APCI) interface according to the conditions of our previous report 20) with the addition of monitoring of 5 ZRC ions (m/z 319 for ZAN and α-or β-ZEL, and 321 for α-or β-ZAL). Detection of ZEN or the 5 ZRCs by LC-MS was confirmed by LC-MS/MS with an electrospray ionization (ESI) interface.…”
Section: Determination Of Mycotoxin Concentration In Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it has been reported that Fusarium isolates from bananas can also produce zearalenone (Jiménez et al, 1997). Table 2 indicates a variety of Fusarium strains which are of great concern as they produce zearalenone in sorghum grain (González et al, 1997;Aoyama et al, 2009). Zearalenone is a mycotoxin of low acute toxicity, but some of its metabolites have high binding affinity for oestrogen receptors, which can result in reproductive problems (cause of infertility, affecting ovulation, conception, implantation, fetal development and the newborn's viability) in all animal species (Aoyama et al, 2009) and can enhance the proliferation of estrogen responsive tumor cells.…”
Section: Zearalenone (Zea)mentioning
confidence: 99%